Compound Flooding Hazards Due To Storm Surge and Pluvial Flow in a Low‐Gradient Coastal Region - Sunghoon Han; Navid Tahvildari (Water Resources Research)
Abstract Flood risk analyses often focus on a single flooding source, typically storm surge or rainfall‐driven flooding, depending on the predominant threat. However, hurricanes frequently cause compound flooding through significant storm surges accompanied by heavy rainfall. This study employs a hydrodynamic model based on Delft3D‐Flexible Mesh that couples flow, waves, and rainfall‐driven flow to simulate five historical tropical cyclones in Virginia's southeast coastal region. These storms produced varying intensities of storm surge and rainfall in the study area. Model simulations, incorporating rainfall through a rain‐on‐grid approach, account for the dynamic interaction between storm tides, and pluvial flow and enable the definition of flood zones as hydrologic, transitional, and coastal zones. This compound flooding model was validated with water level data from in‐water and overland gauges. The results indicate that the magnitude of the coastal zone correlates strongly with the extent of the surge‐inundated area (SIA) obtained from simulations that only considered storm surges. The extent of the transitional zone correlates strongly with the product of SIA and total rainfall. As an additional measure for flood hazards besides water depth, we calculated flow momentum flux at different flood zones to assess potential damage from hydrodynamic loads on structures, vehicles, and pedestrians. A strong correlation was found between the magnitude of the surge and momentum flux. Furthermore, high rainfall rates and winds can cause a significant increase in momentum flux locally. Understanding flood zones and their flow dynamics helps to identify effective flood risk management strategies that address the dominant flood driver.